The Dynamics of Spot and Forward Prices in an Efficient Foreign Exchange Market with Rational Expectations - Stein, Jerome L. (American Economic Review, 1980)
Many papers have examined the of the foreign exchange markets during the current float and during the previous adjustable peg period.' An efficient market is one in which the current price fully reflects all relevant available information concerning the evolution of the system from the conditions prevailing at time t to those that will occur at t+l. The research strategy underlying this set of papers is as follows: If the markets can be shown to be efficient, then the market is setting current rates in a rational manner, given the publicly available information. The unduly fluctuations in the exchange rate2 do not result from the activities of irrational speculators, but result either from the large random shocks that impinge upon the economy or from the erratic behavior of the goverments in affecting the rate of exchange. The types of tests used to evaluate the efficiency of the foreign exchange market have been carried over from the stock market literature; and their results are ambiguous and confusing. Kohlhagen summed up the state of recent research: